PEMBUATAN SEDIAAN MASKER TEPUNG BERAS ORGANIK DAN KAYU MANIS (Cinnamomum burmannii Nees ex Bl) UNTUK MENGOBATI KULIT PADA WAJAH BERJERAWAT - Rudi, Rudi; Sulistyaningtyas, Farah; Ratnasari, Dewi (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2017)
Backgroud: Plants have medicinal properties and used as a medicine in the treatment or prevention of disease. Herbs can cure the disease with minimal side effects because it made from natural ingredients, unlike synthetic drugs which can give side effects either directly or after a long time. Objective: To know the composition of the mask preparation of organic rice flour and cinnamon powder (Cinnamomum burmannii Nees ex Bl). Method: The method used in this research is qualitative descriptive journals gathering in advance of studies on the efficacy of cinnamon powder and organic rice flour for acne prone skin in dosage forms mask.This study attempted 3 samples, the first sample of 10 gr organic rice flour, powdered cinnamon 0,75 gr, 10 ml water. The second sample 10 gr organic rice flour, cinnamon powder 0,5 gr, 10 ml water. The third sample 10 gr organic rice flour, powdered cinnamon 0,25 gr, 10 ml water. results obtained in this study is 10 gr organic rice flour, powdered cinnamon 0,25 gr, 10 ml water. organoleptic testing in this study carried out for 3 weeks with the result that the change in color, smell, taste. Results: The Research obtained in this study is 10 gr organic rice flour, powdered cinnamon 0,25 gr, 10 ml water. Organoleptic test in this study was conducted over three weeks and the results showed no changes in color, taste and smell. Conclusion: It can be concluded organic rice flour and cinnamon powder preparations can be made into powder mask for acne prone skin and can hold for three weeks.